2020
DOI: 10.1038/s41598-019-56630-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiles in serum samples from Acute-On-Chronic Liver Failure patients and miR-25-3p as a potential biomarker for survival prediction

Abstract: Acute-on-chronic liver failure (ACLF) is a condition characterized by acute decompensation of cirrhosis, associated with organ failure(s), and high short-term mortality. The microRNAs or miRNAs are small non-coding RNA molecules, stable in circulating samples such as biological fluids, and the difference in expression levels may indicate the presence, absence and/or stage of the disease. We analyzed here the miRNA profiling to identify potential diagnostic or prognostic biomarkers for ACLF. The major miRNAs di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…Recently, the abnormal expression level of miR-25-3p has been discovered in different diseases gradually. For instance, miR-25-3p was found to be up-regulated in triple-negative breast cancer, osteosarcoma, and gastric cancer [ 12–14 ]; while it was found to be down-regulated in acute-on-chronic liver failure and tongue squamous cell carcinoma [ 15 , 16 ]. In addition, miR-25-3p was proved to be a biomarker for the diagnosis and treatment of many cancers and able to regulate the biological functions of various cells [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the abnormal expression level of miR-25-3p has been discovered in different diseases gradually. For instance, miR-25-3p was found to be up-regulated in triple-negative breast cancer, osteosarcoma, and gastric cancer [ 12–14 ]; while it was found to be down-regulated in acute-on-chronic liver failure and tongue squamous cell carcinoma [ 15 , 16 ]. In addition, miR-25-3p was proved to be a biomarker for the diagnosis and treatment of many cancers and able to regulate the biological functions of various cells [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-25-3p was found to be up-regulated in triple-negative breast cancer, osteosarcoma, and gastric cancer [ 12–14 ]; while it was found to be down-regulated in acute-on-chronic liver failure and tongue squamous cell carcinoma [ 15 , 16 ]. In addition, miR-25-3p was proved to be a biomarker for the diagnosis and treatment of many cancers and able to regulate the biological functions of various cells [ 13 , 15 ]. Besides, miR-25-3p could enhance the proliferation and migration of glioma cells, impair tumorigenesis of gastric cancer and regulate the migration of gastric cancer cells, and promote the pre-metastatic niche formation of colorectal cancer [ 14 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, more and more evidence has suggested that microRNAs (miRNAs) are promising biomarkers due to their high sensitivity and specificity for the diagnosis of various diseases such as viral infections and cancers [14] , [15] , [16] . In addition, the expression pattern of cellular miRNAs, during the acute phase of the disease, is different from the post-acute phase of the disease [17] , [18] . So, it has the ability to be considered as a prognosis biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-related alterations in microRNA expression and function can reflect molecular processes of tumor onset and progression qualifying microRNAs as potential diagnostic and prognostic biomarkers. Current investigations show that miRNAs are detectable in different tissue types and a wide range of biological fluids, either free or trapped in circulating EVs [47,48].…”
Section: Profiling Evs-mirnasmentioning
confidence: 99%